Glaciological Data Collected by the 45th, 46th and 47th Japanese Antarctic Research Expeditions during 2004 - 2007 - MOTOYAMA, Hideaki; FURUKAWA, Teruo; GOTO-AZUMA, Kumiko; TANAKA, Yoichi; FURUSAKI, Atsumu; IGARASHI, Makoto; SAITO, Takeshi; KAMIYAMA, Kokichi (National Institute of Polar Research, 2008)
P(論文) departmental bulletin paper